Burden of Silicosis among stone crushing workers in India - Govindagoudar, M B; Singh, P K; Chaudhry, D; Chaudhary, R; Sachdeva, A; Dhankhar, S; Tyagi, D (Occupational medicine (Oxford), 2022)
In North India, the mining industry is disorganized and profit-driven. It predisposes its workers towards the development of silicosis. Haryana, a major North Indian state, has developed a compensation-rehabilitation policy for mining workers.BACKGROUNDIn North India, the mining industry is disorganized and profit-driven. It predisposes its workers towards the development of silicosis. Haryana, a major North Indian state, has developed a compensation-rehabilitation policy for mining workers.This study is the review of the policy's functioning and limitation from the first 4 years of implementation.AIMSThis study is the review of the policy's functioning and limitation from the first 4 years of implementation.The labour department does surveillance of workers in the mining industry. All suspected cases of silicosis are evaluated by a multidisciplinary team. Based on the final diagnosis, the compensation is decided.METHODSThe labour department does surveillance of workers in the mining industry. All suspected cases of silicosis are evaluated by a multidisciplinary team. Based on the final diagnosis, the compensation is decided.Nearly 5000 workers were screened, and 729 appeared before the medical board. Of these 729, 465 were having silicosis, and their data are presented here (data of 7 patients were missing). All workers were males. The mean age was 44.54 ± 9.6 years, and the mean exposure (work experience) was 17.25 ± 6.7 years. Most of the workers were between the age of 40 and 50 years and had exposure for 10-20 years. Chest radiography examination showed that progressive massive fibrosis (large size type C opacities) was the most common type of presentation (23%). Smaller opacities (p, q, r and s, t, u) were combined for further analysis, given their similar prognostic significance. It was found that age and experience both had a linear and significant correlation with the severity of lung involvement.RESULTSNearly 5000 workers were screened, and 729 appeared before the medical board. Of these 729, 465 were having silicosis, and their data are presented here (data of 7 patients were missing). All workers were males. The mean age was 44.54 ± 9.6 years, and the mean exposure (work experience) was 17.25 ± 6.7 years. Most of the workers were between the age of 40 and 50 years and had exposure for 10-20 years. Chest radiography examination showed that progressive massive fibrosis (large size type C opacities) was the most common type of presentation (23%). Smaller opacities (p, q, r and s, t, u) were combined for further analysis, given their similar prognostic significance. It was found that age and experience both had a linear and significant correlation with the severity of lung involvement.Nearly a quarter of subjects were suffering from the worst type of lung involvement at screening itself. The policy has laid a foundation for the welfare of workers, but there is still a long way to go.CONCLUSIONSNearly a quarter of subjects were suffering from the worst type of lung involvement at screening itself. The policy has laid a foundation for the welfare of workers, but there is still a long way to go.